Pesquisar andarilho: cintilâncias e transbordamentos de uma docência - Garlet, Francieli Regina (2014)
Thoughts about teaching were materialized at this research from places which are not only the teacher's activity. This investigation was permeated by poems, photographs, memories and artistic experimentations one of them being the installation andarilhagens (hikerages), produced from these elements. As a researcher I proposed to sweep the teaching figuration so that alternate possibilities to think teaching could be produced. Two years of Master's Degree were dedicated to experiment a hiking way of research, with no fixed living place, where walking produced the stops, and not the contrary. At the experimental hikerages, whether resting or at movement, there was attention to the scintillances which sprung, and from those, on the stops, I collected the ones which gave me velocity and overflowed my thoughts about teaching. These scintillances were not fixed and, by being that way, sometimes they were dressed as opaque, and many of their requested elements permeated the following pages and also left some voids which may be experimented by the readers who venture leaping onto them. Moving terms and concepts as archive, scintillance, diagram and virtual, this research has insinuated itself into that which can overflow, also leaving an invitation so that its written lines and images can be overflown by those who wish so. May the teaching activity I sought to overflow at the following pages continue to overflow at the encounters it may have from now on.